Persepsi Orang Tua Terhadap Pembelajaran Daring Di Masa Pandemi Covid-19 Dini di Taman Kanak-Kanak Kecamatan Pinolosian Kabupaten Bolaang Mongondow Selatan - Amu, Sofyan; Fathimah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The emergence of COVID-19 has created unprecedented challenges for the world. In Indonesia, the coronavirus has infected more than four million people since the first confirmed case in March 2020 and hundreds of thousands of people have died. The COVID-19 pandemic has devastated economic development and the continued development of human resources, especially education. To break the chain of transmission of COVID-19, more than 120 countries have imposed social distancing restrictions through school closures which impacted 1.6 billion students worldwide. In Indonesia, the government closed all schools and instruct online learning schools as an alternative solution so that the teaching and learning process continues. Parents play an important role in the running of online learning. Positive parental perceptions of online learning have implications for parental support to directly supervise their children's learning. However, technical constraints such as lack of information communication technology infrastructure such as smartphones and internet connections. In addition, the educational background of parents also affects the motivation of parents to be more active in supporting their children's online learning.